Identification of novel modulators of a schistosome transient receptor potential channel targeted by praziquantel. - Evgeny G Chulkov; Emery Smith; Claudia M Rohr; Nawal A Yahya; Sang-Kyu Park; Louis Scampavia; Timothy P Spicer; Jonathan S Marchant (Public Library of Science (PLoS), 2021)
Given the worldwide burden of neglected tropical diseases, there is ongoing need to develop novel anthelmintic agents to strengthen the pipeline of drugs to combat these burdensome infections. Many diseases caused by parasitic flatworms are treated using the anthelmintic drug praziquantel (PZQ), employed for decades as the key clinical agent to treat schistosomiasis. PZQ activates a flatworm transient receptor potential (TRP) channel within the melastatin family (TRPMPZQ) to mediate sustained Ca2+ influx and worm paralysis. As a druggable target present in many parasitic flatworms, TRPMPZQ is a promising target for a target-based screening campaign with the goal of discovering novel regulators of this channel complex. Here, we have optimized methods to miniaturize a Ca2+-based reporter assay for Schistosoma mansoni TRPMPZQ (Sm.TRPMPZQ) activity enabling a high throughput screening (HTS) approach. This methodology will enable further HTS efforts against Sm.TRPMPZQ as well as other flatworm ion channels. A pilot screen of ~16,000 compounds yielded a novel activator of Sm.TRPMPZQ, and numerous potential blockers. The new activator of Sm.TRPMPZQ represented a distinct chemotype to PZQ, but is a known chemical entity previously identified by phenotypic screening. The fact that a compound prioritized from a phenotypic screening campaign is revealed to act, like PZQ, as an Sm.TRPMPZQ agonist underscores the validity of TRPMPZQ as a druggable target for antischistosomal ligands.